2021
DOI: 10.1038/s41467-021-24622-7
|View full text |Cite|
|
Sign up to set email alerts
|

SARS-CoV-2 antibody dynamics and transmission from community-wide serological testing in the Italian municipality of Vo’

Abstract: In February and March 2020, two mass swab testing campaigns were conducted in Vo’, Italy. In May 2020, we tested 86% of the Vo’ population with three immuno-assays detecting antibodies against the spike and nucleocapsid antigens, a neutralisation assay and Polymerase Chain Reaction (PCR). Subjects testing positive to PCR in February/March or a serological assay in May were tested again in November. Here we report on the results of the analysis of the May and November surveys. We estimate a seroprevalence of 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
39
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 35 publications
(31 reference statements)
11
39
0
3
Order By: Relevance
“…In our study, sensitivity of the test in the subset of patients >60 days from symptom onset was 88%, indicating that IgG responses can be tracked in individuals during the first two months. This coincides with previous reports of a median half-life of antibodies detected by Abbott of 86 days [ 35 ], and a decay in seropositivity after 90 days reported in a Brazilian population evaluated with this test [ 39 ]. These aspects should be considered when analyzing and interpreting serosurveys conducted globally with the Abbott assay, since the true cumulative number of SARS-CoV-2 infections may be underestimated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, sensitivity of the test in the subset of patients >60 days from symptom onset was 88%, indicating that IgG responses can be tracked in individuals during the first two months. This coincides with previous reports of a median half-life of antibodies detected by Abbott of 86 days [ 35 ], and a decay in seropositivity after 90 days reported in a Brazilian population evaluated with this test [ 39 ]. These aspects should be considered when analyzing and interpreting serosurveys conducted globally with the Abbott assay, since the true cumulative number of SARS-CoV-2 infections may be underestimated.…”
Section: Discussionsupporting
confidence: 92%
“…Decline of antibody titers and seropositivity has been reported for different tests, including the Abbott IgG [ 30 , 35 38 ]. In our study, sensitivity of the test in the subset of patients >60 days from symptom onset was 88%, indicating that IgG responses can be tracked in individuals during the first two months.…”
Section: Discussionmentioning
confidence: 99%
“…The team found that 98.8% of people infected in February/March showed detectable levels of antibodies in November, and there was no difference between people who had suffered symptoms of COVID-19 and those who had been symptom-free. The results showed that while all antibody types showed some decline between May and November, the rate of decay was different depending on the assay ( 19 ). Interestingly, after COVID vaccination, neutralization capacity was different from natural infection ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, we found that titres of neutralizing antibodies were sustained at a similarly high, protective level at 4 months after infection, irrespective of symptomatic or asymptomatic disease 52 . Similarly, a longitudinal serological analysis of inhabitants of Vo’ found no difference in antibody responses in individuals with either symptomatic or asymptomatic infection 53 . A 10-month longitudinal analysis of 963 individuals with either symptomatic or asymptomatic disease investigated the durability of neutralizing antibody responses in more detail 54 .…”
Section: Immunity After Asymptomatic Primingmentioning
confidence: 96%